Social media use and its association with sexual practices among undergraduate students in a private medical university at Solan, Himachal Pradesh - Arjit Kumar (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Social networking has become integral to the intellectual and social lives of the young populace. Their often unrestricted access to sexually explicit content and associated adverse sexual health constitute key outcomes in public health research. Objectives: To determine the association between social media use and various sexual practices among undergraduate students in a private medical university at Solan, Himachal Pradesh. Methods: We enrolled 300 undergraduates, using random sampling technique in the present cross sectional study. Data were collected using semi-structured questionnaire and data analysis employed statistical package for social sciences version 22.0. Chi-square test was used to determine association between variables and p value<0.05 was considered as statistically significant. Results: The mean age of respondents was 21.85+ 2.63 years. Majority of the respondents have heard about social media (n=299, 99.7%) and majority have received information from friends/peers (79%). The commonest reason for non-use of social media for sexually explicit content was lack of interest (54.3%). The mean age at sexual debut was 17.44 + 2.63 years. There was statistically significant association between use of social media for sexually explicit content and being sexually active (p=0.000), type of sexual acts practiced (p=0.003) and number of sexual partners (p=0.000). Conclusion: There is need for improved multi- sectoral measures (formal comprehensive sex education, peer education programs, school mini-media clubs and targeted behavior change intervention), Media and internet literacy education to control viewing of social media for sexually explicit content, while ensuring that young people's access to sexual health educational content is not compromised.